Division blocks in temperature-sensitive mutants of Streptococcus faecium (S. faecalis ATCC 9790). - Canepari, P (1983)
Two hundred nine temperature-sensitive growth or division (or both) mutants of Streptococcus faecium ATCC 9790 were isolated. These strains were examined for timing of the division block in the cell division cycle. About 42% of the isolates were blocked at terminal stages of cell division. A second large group appeared to be blocked at various stages of septation. Only five of the temperature-sensitive isolates were blocked at a stage before the completion of chromosome replication. Thirty temperature-sensitive isolates lysed after one or more doublings at the nonpermissive temperature.